Patterns of biblical dates and Qumran's calendar: The fallacy of Jaubert's hypothesis - Wacholder, Ben Zion (Hebrew Union College annual / Jewish Institute of Religion, 1995)
The Hebrew Scriptures rarely date events, with only some sixty episodes from the flood to the visions of Ezekiel being chronicled. Students of the Bible have long speculated what mode of reckoning time lies behind these dates. In 1953, Annie Jaubert according to general opinion resolved this riddle. Taking the model from the calendar prescribed by the author of the Book of Jubilees, Jaubert proposed that the biblical chronologists must have dated according to Jubilean calendation. Analyzing these dated episodes in the Hebrew Scriptures, Jaubert found a remarkable pattern. If the biblical points of time are translated into Jubilean dates, a picture is formed of an idealized Jewish week. Activity such as traveling would start on Sunday, other actions on Wednesday, but all would be completed on Friday with the Sabbath as a day of rest. In other words, either the ancient Jews were scrupulously observing the day of the Lord or their master chronicler made them do so. This paper refutes Jaubert's hypothesis arguing that: 1) Jaubert supposes that the biblical dates are random, when in fact they have definite patterns; 2) a number of biblical passages reflect the use of a lunisolar calendar rather than the schematic calendation of the Jubilean reckoning; and 3) contrary to biblical stipulation which links Passover to the spring, the Jubilean reckoning would make Passover cycle throughout the year.